2006
DOI: 10.1016/j.jcrs.2006.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Scheimpflug measurement of intraocular lens position after piggyback implantation of foldable intraocular lenses in eyes with high hyperopia

Abstract: Piggyback IOL implantation with placement of 2 foldable IOLs in the capsular bag can be followed by a hyperopic shift that may be caused in part by displacement of the IOLs. Placement of the anterior IOL in the ciliary sulcus can lead to higher decentration of this IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
0
13
1
2
Order By: Relevance
“…8,9 Several methods to prevent ILO, including creation of a relatively large capsulorhexis and implantation of the piggyback IOL in the ciliary sulcus rather than in the capsular bag, have been shown to decrease the incidence of this complication. 21 However, implantation of a piggyback IOL in the ciliary sulcus may be associated with a different set of complications, such as pigmentary dispersion syndrome. 5-7 A previous publication from our laboratory 7 described a case of pigmentary dispersion syndrome resulting from secondary piggyback implantation of a 3-piece hydrophobic acrylic, square-edged IOL in the ciliary sulcus.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Several methods to prevent ILO, including creation of a relatively large capsulorhexis and implantation of the piggyback IOL in the ciliary sulcus rather than in the capsular bag, have been shown to decrease the incidence of this complication. 21 However, implantation of a piggyback IOL in the ciliary sulcus may be associated with a different set of complications, such as pigmentary dispersion syndrome. 5-7 A previous publication from our laboratory 7 described a case of pigmentary dispersion syndrome resulting from secondary piggyback implantation of a 3-piece hydrophobic acrylic, square-edged IOL in the ciliary sulcus.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, implanting 1 IOL in the capsular bag and a second in the sulcus produces better results. 37 Intraocular lenses placed in the sulcus that are not designed for sulcus fixation are not shaped to prevent contact with the capsular bag IOL, which can lead to unstable fixation, iris irritation, and chronic intraocular inflammation. [38][39][40] The posterior concave optic of the diffractive multifocal add-on IOL we used prevents contact with the capsular bag IOL because the rounded optic edge and the design of the optical zone do not cause iris irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright: to assess IOL tilt and decentration in vivo, using either Purkinje meters [33][34][35][36][37] or Scheimpflug imaging [38,39]. To assess tilt and decentration in relation to HOAs after implantation of an aspheric IOL in patients, clinical studies were conducted [40,41] and it was shown that the limits for tilt and decentration for proper functioning of AIOLs found in laboratory studies were respected after AIOL implantation in vivo, resulting in a reduction of total SA.…”
Section: /3mentioning
confidence: 99%